2020
DOI: 10.1080/09650792.2020.1850497
|View full text |Cite
|
Sign up to set email alerts
|

Visible mathematics pedagogy: A model for transforming classroom practice

Abstract: This paper focuses on the development of a model of research and professional development which aims to bring about transformations in classroom practice in situations that have previously proved resistant to change. We explore the reasons why conventional approaches to research have failed to address one such situation, the continuing predominance of teacher-centred pedagogies in mathematics classrooms. We review conventional models of professional development from the perspective of teacher agency and engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The teacher-researchers can also help facilitate RPP projects that serve as professional learning for interested teacher colleagues. Studies have suggested that involvement in participatory action research helps improve teachers’ professional practices (Miedijensky & Sasson, 2022; Wright, Carvalho, & Fejzo, 2022). Teachers want professional learning that (1) is teacher-led, (2) offers interaction and is pertinent to their students, (3) is practical for classroom needs, and (4) has continuity (Matherson & Windle, 2017).…”
Section: Infrastructure Of An Rpp Advancement Pathwaymentioning
confidence: 99%
“…The teacher-researchers can also help facilitate RPP projects that serve as professional learning for interested teacher colleagues. Studies have suggested that involvement in participatory action research helps improve teachers’ professional practices (Miedijensky & Sasson, 2022; Wright, Carvalho, & Fejzo, 2022). Teachers want professional learning that (1) is teacher-led, (2) offers interaction and is pertinent to their students, (3) is practical for classroom needs, and (4) has continuity (Matherson & Windle, 2017).…”
Section: Infrastructure Of An Rpp Advancement Pathwaymentioning
confidence: 99%